Perbandingan Selisih Harga Pada Kontrak Harga Satuan Dan Lumsum: Pendekatan Ekonomi Biaya Transaksi - Linda Mikowati; Yohanna Magdalena Lidya Gultom (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
This study compares two major types of contracts in public procurement, i.e. unit price and lump sum contracts, in terms of the gap between the winner's bid price and owner’s estimated price (OEP) in resulted price gap during the tender process, taking the case of government procurement in Indonesia. Using Indonesian e-tendering data of 2018-2021, this study employs an Ordinary Least Square regression to assess whether there is a difference in the price gap between the two types of contracts. This study finds that the average price gap in unit price contract is significantly higher than that of lump sum contracts. With the help of the transaction cost economics approach, this study discussed that the higher average price gap in unit price contracts is related to a lower information cost and lower risk of having a change order for the contract faced by the bidders. While in a lump sum contract, the winner's bid price is closer to OEP because bidders are faced with design risks that require higher information costs and contract adaptation during the execution phase. The study also found that the use of a unit price contract is significantly related to a longer tendering time due to a longer period in evaluating the bid.